Zinc Signaling in Physiology and Pathogenesis - Toshiyuki Fukada (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The essential trace element zinc plays indispensable roles in multiple cellular processes. It regulates a great number of protein functions, including transcription factors, enzymes, adapters, and growth factors as a structural and/or catalytic factor. Recent studies have highlighted another function of zinc as an intra- and intercellular signaling mediator, which became recognized as the "zinc signal". Indeed, zinc regulates cellular signaling pathways, which enable conversion of extracellular stimuli to intracellular signals, and controls various intracellular and extracellular events, and thus zinc mediates communication between cells. The zinc signal is essential for physiology, and its dysregulation causes a variety of diseases, such as diabetes, cancer, osteoarthritis, dermatitis, and dementia. This Special Issue focuses on crucial roles of zinc signaling in biological processes in molecular and physiological basis, addressing the future directions and questions underlying this unique phenomenon. Because there is growing interest and attention in physiopathological contribution of zinc signal, we believe this Special Issue will provide very timely information on it and thus should appeal to a wide range of readers.